A Review on Terminalia chebula Retz. (Harar)- An Important Multipurpose Tree - Singh, Samanpreet; Bhatia, Avinash Kumar; Sharma, Kamal; Sharma, Dushyant (International Journal of Economic Plants, 2020)
Terminalia chebula Retz. commonly known as ‘Harar’ belongs to the family Combretaceae. It is found in deciduous forests throughout the greater part of India, China, Myanmar, Sri Lanka, Vietnam, Bangladesh, etc. In India, it is distributed throughout the greater part except in arid zones. The fruits are common constituent of ‘Triphala’, capable of imparting youthful vitality and receptivity of mind and sense and are extensively used for clinical research, tanning and furniture purposes and also contain 1.73% nitrogen and 2.75% Calcium. The demand for its fruit has increased tremendously, because of its medicinal value; its fruits are sold at a price of Rs. 10-60 kg-1. However, the poor germination capacity, lack of natural regeneration and knowledge regarding its propagation are the limiting factors for its adoption in agroforestry systems. There is need of more productive planting stock with lower juvenile period and comparatively large fruit size.